The effect of xylen on the lung in the rat: An ultrastructural study - Kukner, A.; Canpolat, L.; Gokcimen, A.; Ozan, E.; Ozan, S. (My University, 1995)
[Abstract Not Available]
Keywords: xylene; animal experiment; conference paper; connective tissue; electron microscopy; eosinophil; fibroblast; lung; macrophage; nonhuman; rat; ultrastructure